(i) a6 – b6
Above terms can be written as,
(a2)3 – (b2)3
We know that, a3 – b3 = (a – b) (a2 + ab + b2)
So, a = a2, b = b2
(a2 – b2) ((a2)2) + a2b2 + (b2)2)
(a2 – b2) (a4 + a2b2 + b4)
(ii) x6 – 1
Above terms can be written as,
(x2)3 – 13
We know that, a3 – b3 = (a – b) (a2 + ab + b2)
So, a = x2, b = 1
(x2 – 1) ((x2)2 + (x2 × 1) + 12)
(x2 – 1) (x4 + x2 + 1)
More Solutions:
- Factorisation of p4 – 81² is
- Factorisation of x²- 4x-12 is
- The factorization of 4x² 8xr +3 is
- Factorisation of r2 – 4xy + 4y2 is
- Factorise 15(2x – 3)3 – 10(2x – 3)
- Factorise 2a2x – bx + 2a2 – b
- Factorise (x2 – y2)z + (y2 – z2)x
- Factorise b(c -d)2 + a(d – c) + 3c – 3d
- Factorise x(x + z) – y (y + z)
- Factorise 9×2 + 12x + 4 – 16y2